Ultrasonic treatment as the route for grain refinement of Mg-al alloys: a systematic review - Gomes, Inês Varela (2021)
In this work, a systematic review of the published literature was conducted, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, on the ultrasonic treatment of magnesium-aluminium alloys for grain refinement. Scopus, Science Direct, and Web of Science databases were used in the literature search, which was finished by the 1st of June 2021. Seventeen articles met the eligibility criteria and were considered in this review, organized according to the type of ultrasonic treatment applied: isothermal (8/17) or continuous (9/17). Summary tables were used to categorize the information gathered from the articles, namely Treatment Conditions, Microstructural and Mechanical Analysis, and Mechanisms Behind Ultrasonic Grain Refining Ability. This systematic review aimed to structure and organize the available information regarding the ultrasonic processing of magnesium-aluminium alloys so new researchers can find a start point for their works and identify potential gaps in this research field.